Analysis Of Sales Forecasting For Goods At UD LUKI In Nias Utara - Wardin Nofanolo Laoli; Idarni Harefa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims paper is a valuable resource for decision-makers, researchers, and practitioners interested in enhancing sales forecasting capabilities through a blend of data-driven analysis and strategic innovation. Integrating advanced LSTM neural networks with expert qualitative insights significantly enhances UD LUKI’s sales forecasting accuracy. This hybrid approach not only captures complex trends and adapts to external market fluctuations but also supports better inventory management and strategic decision-making. Ultimately, continuous refinement and collaborative practices are essential for maintaining a competitive edge in the dynamic Nias Utara market.